COVID-19 lockdown related to decrease in premature birth rate and increase in birth weight in metropolitan France - Tessier, Benoit; Annesi-Maesano, Isabella; Cambonie, Gilles; Molinari, Nicolas; Kalfa, Nicolas (Frontiers in Pediatrics, 2023)
Introduction The worldwide rate of preterm birth (PTB) has been increasing over the last two decades. COVID-19 lockdowns provide a unique opportunity to assess the effects of socioenvironmental and lifestyle factors on premature birth and birth weight. We explored the effects of COVID-19 lockdowns on the PTB rate and birth weight at a nationwide scale in France until one year after their occurrence. Material and Methods This national retrospective observational study evaluated the rate of PTB and birth weight in France from January 2016 to December 2020. Data were obtained from the national Programme Médicalisé des Systèmes d'Information database. The rates of global and sub-categories of PTB were tested. The birth weight was studied before and after lockdown for all live births, for term and premature neonates, and for each category of low birth weight (LBW) by a stratified analysis. Results Data from 2,949,372 births from January 2016 to December 2019, including 228,857 PTB, were compared to those of 699,344 births and 51,886 PTB from January to December 2020. The national rate of PTB decreased significantly from 7.7% to 7.3%, when compared with the 2016–2019 period. This decrease was persistent up to 9 months later. It was observed only for moderate PTB, whereas very PTB and extremely PTB remained stable. The national mean birth weight for full-term babies increased after the lockdown and was still observable up to 8 months later (+0.16%, p < 0.0001). The proportion of children with LBW also decreased 2 months after lockdown (−0.15%; p = 0.02). For VLBW, the difference only appeared over the 6-month post-lockdown period (−0.06%; p = 0.006). Conclusion This nationwide study shows a significant reduction in prematurity and a significant increase in birth weight in France after the lockdown for a period of time not limited to the lockdown itself. A more in-depth study of the factors determining these variations may help to drive PTB prevention policies.